Randomized Control Trial Study On The Effect Of Wet Cupping On Lipid Profile - MH, Suhaily; AA, Ismail; MY, Najib (IIUM Medical Journal Malaysia, 2017)
Introduction: Dyslipidaemia is one of the risk factors contributing to the pathogenesis of cardiovascular diseases (CVDs). This study was conducted to investigate the effect of wet cupping on lipid profile. Methods: This randomized controlled trial was conducted in 2012 at the School of Medical Sciences, Universiti Sains Malaysia, Malaysia. Sixty-two healthy volunteers ranging from 30 to 60 years old were randomized into control and intervention groups. Subjects in the intervention group were assigned to two sessions of wet cupping at the beginning of the study and at the third month; individuals in the control group did not undergo any cupping procedure. Venous blood sample was collected for serum lipid profile: Total Cholesterol (TC), High Density Lipoprotein Cholesterol (HDL-C), Low Density Lipoprotein Cholesterol (LDL-C), and triglycerides; measured at baseline, first, third and fourth month. Results: Subjects in the cupping group had significant improvements from baseline to third and fourth month for TC (MD=-0.56, P=0.004), HDL-C (MD=-0.22, P<0.001) and LDL-C (MD=0.58, P=0.001). There was also a significant reduction from baseline to one month for triglycerides (MD=0.38, P<0.001). Subjects in the cupping group had significantly better values in HDL-C and LDL-C as compared with the control group at the third and fourth month. Significantly lower levels of TC and triglycerides in the cupping group of the fourth month. In the control group, there were no significant changes in any serum lipid profiles. Conclusion: After two sessions of wet cupping, TC, HDL-C, LDL-C and triglycerides were significantly improved by 8.2%, 13.7%, 16.4% and 20.8% respectively.